(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, a theoretical analysis was carried out, which provided for clarifying the essence and content of the term "akmelinguistics" of students in universities of various profiles. As the main features of akmelinguistics, the principles of the acquisition by an individual of the achievement of the acme level through language, the activity of the speech form are determined. The improvement of all types of communication in a speech format as a cultural and linguistic space in all kinds of situations of speech activity is defined as the basic position of mastering the axelinguistic competence by students in universities as a certain list of personal qualities, as well as personality characteristics that can be used by it for effective activity in the professional aspect.